Cerebral cavernous malformation protein CCM1 inhibits sprouting angiogenesis by activating DELTA-NOTCH signaling - Wüstehube-Lausch, Joycelyn; Bartol, Arne; Liebler, Sven Stefan; Brütsch, René Michael; Zhu, Yuan; Felbor, Ute; Sure, Ulrich; Augustin, Hellmut; Fischer, Andreas (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cerebral cavernous malformations (CCM) are frequent vascular abnormalities caused by mutations in one of the CCM genes. CCM1 (also known as KRIT1) stabilizes endothelial junctions and is essential for vascular morphogenesis in mouse embryos. However, cellular functions of CCM1 during the early steps of the CCM pathogenesis remain unknown. We show here that CCM1 represents an antiangiogenic protein to keep the human endothelium quiescent. CCM1 inhibits endothelial proliferation, apoptosis, migration, lumen formation, and sprouting angiogenesis in primary human endothelial cells. CCM1 strongly induces DLL4-NOTCH signaling, which promotes AKT phosphorylation but reduces phosphorylation of the mitogen-activated protein kinase ERK. Consistently, blocking of NOTCH activity alleviates CCM1 effects. ERK phosphorylation is increased in human CCM lesions. Transplantation of CCM1-silenced human endothelial cells into SCID mice recapitulates hallmarks of the CCM pathology and serves as a unique CCM model system. In this setting, the multikinase inhibitor Sorafenib can ameliorate loss of CCM1-induced excessive microvascular growth, reducing the microvessel density to levels of normal wild-type endothelial cells. Collectively, our data suggest that the origin of CCM lesions is caused by perturbed Notch signaling-induced excessive capillary sprouting, which can be therapeutically targeted.
Gesehen am 22.05.2024